(untitled) (Journal of Fatima Jinnah Medical University, 2024)
Background: Hepatic encephalopathy is a serious complication of liver disease, marked by cognitive impairment and potentially life-threatening consequences. Lactulose has long been a standard treatment, but its effectiveness may be limited. Adding rifaximin to lactulose has shown promising results in managing overt hepatic encephalopathy (OHE). This study compared the frequency of complete reversal of encephalopathy by rifaximin plus lactulose versus lactulose alone in patients with OHE. Patients and methods: A randomized controlled trial was carried out at Gastroenterology, DHQ, Gujranwala. The patients diagnosed with hepatic encephalopathy (age range = 18-60 years) were included. On the contrary, patients with serum creatinine of >1.5 mg/dl at admission, diagnosed with hepatocellular carcinoma, active alcohol intake (<4 weeks) and patients with significant comorbidities like CVA, epilepsy, and dementia were excluded from the study were not included in the study. Ninety patients into two equal groups; Group A-B. A patients received a combination therapy of Rifaximin (550mg tablet twice daily) and lactulose (30-60 ml thrice a day). Group B patients received lactulose (30-60 ml thrice times daily) placebo capsule (sugar) thrice daily. Both groups were monitored for achievement of optimal bowel function (two to three semisoft stools per day). Results: The patients was 44.9 years. Overall there were 66 (73.3%) males 24 (26.7%) females. The mean MELD scores in group A-B were 33.76 ± 16.76 and 34.36 ± 15.85. The mean duration of liver cirrhosis in group A and group B was 6.49 ± 2.25 and 6.67 ± 2.40, respectively. In group A, a complete reversal of HE was seen in 38 (84.4%) cases while in group B the complete reversal of HE was observed in 24 (53.3%) cases (p-value <0.05). Conclusion: The combination of Rifaximin with lactulose is more effective in treating overt hepatic encephalopathy compared to lactulose alone in terms of complete reversal.